The logic of transnational outbidding: Pledging allegiance and the escalation of violence. (May 2020) - Farrell, Megan
The phenomenon of outbidding, in which terrorist groups escalate their attacks in response to competition from other groups, has long been studied in a domestic terrorism context. If groups exist in the same state, they may compete with one another for the same resources from civilians of that state. This article argues this outbidding logic also exists in a transnational context. Leveraging a sample of Salafi-jihadist groups that are in competition for resources based on shared ideology, this article explores the full effects of this competition on the quantity and severity of groups' attacks. Building on this outbidding logic as a theoretical lens, Salafi-jihadist groups adjust their attack profiles in response to competition from other groups following this same ideology. This effect is particularly evident among groups that pledge allegiance to al-Qaeda or ISIS. Once pledged, affiliates must now compete with other affiliates for the additional potential resources and recruits who follow the 'brand' of al-Qaeda or ISIS. Consistent with this theory, after examining the attacks of all Salafi-jihadist groups from 2001 to 2014, this article finds increased competition among groups results in more attacks and a selection of more severe targets and types of attacks. Affiliate groups respond to competition to the greatest degree.